2011
DOI: 10.4161/gmic.2.2.15414
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery is associated with celiac disease but not inflammatory bowel disease in children

Abstract: The postnatal period represents a particularly dynamic phase in the establishment of the host-microbial homeostasis. The sterile protected intestinal mucosa of the fetus becomes exposed to and subsequently colonized by a complex and diverse bacterial community. Both, the exposure to microbial ligands and the bacterial colonization have been described to differ between neonates born vaginally or by cesarean delivery. These differences might influence the development of the mucosal immune system, the establishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 84 publications
6
136
0
9
Order By: Relevance
“…In 1987, Kagnoff et al suggested that adenovirus may play a role in the pathogenesis of CD,12 and prior rotavirus infection increases the risk of developing CD13 but not active infection 14. A recent German study found that earlier gastrointestinal disease (including both infections and non-infectious disease) increased the risk of later CD,15 while our group found a non-significantly increased risk of CD in children with an infection at the time of gluten introduction 8. Recently we also showed that elective caesarean section is associated with later CD 16.…”
Section: Introductionsupporting
confidence: 41%
“…In 1987, Kagnoff et al suggested that adenovirus may play a role in the pathogenesis of CD,12 and prior rotavirus infection increases the risk of developing CD13 but not active infection 14. A recent German study found that earlier gastrointestinal disease (including both infections and non-infectious disease) increased the risk of later CD,15 while our group found a non-significantly increased risk of CD in children with an infection at the time of gluten introduction 8. Recently we also showed that elective caesarean section is associated with later CD 16.…”
Section: Introductionsupporting
confidence: 41%
“…Additionally, by age 11 these children were 1.83 times more likely to be overweight or obese (65). Furthermore, Decker et al found that children born by cesarean section also have an enhanced risk for developing celiac disease (66). Gut microbial dysbiosis has been the most accepted explanation for the association of delivery mode with disease outcome, but more research is needed to adequately support these hypotheses, as these remain as association studies.…”
Section: Factors That Influence the Development Of The Gut Microbiotamentioning
confidence: 99%
“…During infancy, the impact of alterations in community assembly on function has been linked to outcomes such as malnourishment, C. difficile -associated diarrhea, and necrotizing enterocolitis (74,76,77). Early life microbiome disruption may potentially increase risk for developing celiac disease, asthma, type-1 diabetes, and obesity (70,72,78-81). These conditions could have long-term medical implications that interact reciprocally with the gut microbiome.…”
Section: The Infant Microbiome and Transgeneration Effectsmentioning
confidence: 99%